2021
DOI: 10.1021/acsapm.1c00539
|View full text |Cite
|
Sign up to set email alerts
|

Electrospinning Fabrication of Europium-Chain@polymer Nanofiber Films for Visual Detection of the Fe3+ Ion

Abstract: A ternary europium­(III) coordination polymer, namely, [Eu­(ctpy)­(tta)2] n (1) (Hctpy = 4′-carboxy-2,2′:6′,2″-terpyridine and Htta = 2-thenoyltrifluoroacetone), was obtained and exhibits a 1D chain structure. 1-Eu emits intense red light, which can act as a luminescent dopant to be immobilized into polymers to prepare nanofiber films by an electrospinning technique. Subsequently, ternary europium-chain@polymer nanofiber films (1-Eu@PAN and 1-Eu@PMMA, PAN = polyacrylonitrile, PMMA = poly­(methyl methacrylate)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…At the same time, the N 1s peak shifted from 399.65 to 400.02 eV (Figure S9). Cu 2+ is an unsaturated electron configuration, which may interact with terpyridyl groups with rich electrons in the ligand L, so some electrons (or charges) transfer to Cu 2+ ions, which affects the coordination in the Cd-nanosheet and causes the change of binding energy, eventually leading to the luminescence quenching of the Cd-nanosheet. …”
Section: Resultsmentioning
confidence: 99%
“…At the same time, the N 1s peak shifted from 399.65 to 400.02 eV (Figure S9). Cu 2+ is an unsaturated electron configuration, which may interact with terpyridyl groups with rich electrons in the ligand L, so some electrons (or charges) transfer to Cu 2+ ions, which affects the coordination in the Cd-nanosheet and causes the change of binding energy, eventually leading to the luminescence quenching of the Cd-nanosheet. …”
Section: Resultsmentioning
confidence: 99%
“…The sensor exhibits excellent selectivity and sensitivity for iron ions with a detection limit of 63 nM. Bai et al 98 doped a chain complex (1-Eu 3+ ) formed by Eu 3+ and organic molecular ligands into PAN solution, and fabricated an iron ion-responsive nanofibrous membrane sensor (1-Eu 3+ @PAN). The sensor showed obvious red fluorescence quenching under iron ion treatment, and the detection limit was 6.685 × 10 −4 M.…”
Section: Electrospun Nanofiber Fluorescent Sensor For Detection Of Ha...mentioning
confidence: 99%
“…Luminescent metal–organic frameworks (LMOFs) are hybrid materials with porous structures assembled by organic connectors and metal cations through coordination bonds. LMOFs have been widely implemented in various fields such as gas absorption and separation, fluorescence detection, biological imaging, and photocatalytic degradation of organic pollutants . Sheldrick et al reported Eu-MOFs that can selectively sense Fe 3+ through fluorescence quenching .…”
Section: Introductionmentioning
confidence: 99%